The relationship between intestinal microbiota and polycystic ovary syndrome - Katarzyna Korabiusz; Agata Wawryków; Anna Fabian- Danielewska; Monika Stecko; Patrycja Piątek; Magdalena Żukowska (Journal of Education, Health and Sport, 2019)
Introduction: PCOS is a hyperandrogenic and low-pathogenic disease and patients suffering from PCOS have significantly lower intestinal microbiota variation in comparison with healthy individuals. Aim of the study:The aim of the work is to overview the literary production regarding reliance between intestinal microbiota and polycystic ovary syndrome. Conclusions: Results of the research show change in microbiome data amongst women suffering from polycystic ovary syndrome.